Implementasi Konsep Akhlak Tasawwuf Dalam Pendidikan Agama Islam (Studi Analisis Degradasi Moral) - Wahidah, Evita Yuliatul; Herianto, Adrian (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Sufi ethics, or "akhlak tasawuf," is essential in today’s era of globalization as a means to mitigate moral degradation and address the gaps in human behavior towards oneself, fellow humans, and Allah SWT. Within Islamic Religious Education (PAI), the teachings of Sufi ethics emphasize spiritual growth and heart management. Generally, Sufi ethics instills religious spiritual values that foster noble moral behavior. Such noble behavior holds the promise of establishing a progressive civilization that does not neglect the divine values inherent in human life. Therefore, it is crucial to discuss the concept of Sufi ethics in PAI education as a solution to the ongoing moral degradation in society, aiming to cultivate noble character. The objective of this study is to manifest the implementation of Sufi ethical teachings in Islamic Religious Education, particularly fostering praiseworthy morals. This study adopts a qualitative library research approach, utilizing descriptive-analytical methods to analyze and describe conditions, thoughts, or facts. Once these data are described, they facilitate the formation of a cohesive concept of Sufi ethics integrated into the PAI educational process. The findings of this study highlight the implementation of a Sufi ethical framework within Islamic Religious Education, characterized by religious and spiritual values, to cultivate noble behavior towards Allah SWT, oneself, fellow humans, and all living beings in the universe.  Keywords: Concept of Sufi Ethics, Islamic Religious Education, Moral Degradation